Specific and Stable Suppression of HIV Provirus Expression In Vitro by Chimeric Zinc Finger DNA Methyltransferase 1 - Junxiao Deng; Xiying Qu; Panpan Lu; Xinyi Yang; Yuqi Zhu; Haiyan Ji; Yanan Wang; Zhengtao Jiang; Xian Li; Yangcheng Zhong; He Yang; Hanyu Pan; et al. (Elsevier, 2017)
HIV-1 inserts its proviral DNA into the infected host cells, by which HIV proviral DNA can then be duplicated along with each cell division. Thus, provirus cannot be eradicated completely by current antiretroviral therapy. We have developed an innovative strategy to silence the HIV provirus by targeted DNA methylation on the HIV promoter region. We genetically engineered a chimeric DNA methyltransferase 1 composed of designed zinc-finger proteins to become ZF2 DNMT1. After transient transfection of the molecular clone encoding this chimeric protein into HIV-1 infected or latently infected cells, efficient suppression of HIV-1 expression by the methylation of CpG islands in 5'-LTR was observed and quantified. The effective suppression of HIV in latently infected cells by ZF2-DNMT1 is stable and can last through about 40 cell passages. Cytotoxic caused by ZF2-DNMT1 was only observed during cellular proliferation. Taken together, our results demonstrate the potential of this novel approach for anti-HIV-1 therapy. Keywords: HIV-1, methylation, zinc finger, chimeric protein, DNMT1, gene therapy